Comparison of grey matter volume and thickness for analysing cortical changes in chronic schizophrenia: a matter of surface area, grey/white matter intensity contrast, and curvature - Kong, Li; Herold, Christina; Zöllner, Frank G.; Lässer, Marc; Schmid, Lena A.; Fellhauer, Iven; Thomann, Philipp; Essig, Marco; Schad, Lothar R.; Schröder, Johannes (Psychiatry research, 2015)
Grey matter volume and cortical thickness are the two most widely used measures for detecting grey matter morphometric changes in various diseases such as schizophrenia. However, these two measures only share partial overlapping regions in identifying morphometric changes. Few studies have investigated the contributions of the potential factors to the differences of grey matter volume and cortical thickness. To investigate this question, 3T magnetic resonance images from 22 patients with schizophrenia and 20 well-matched healthy controls were chosen for analyses. Grey matter volume and cortical thickness were measured by VBM and Freesurfer. Grey matter volume results were then rendered onto the surface template of Freesurfer to compare the differences from cortical thickness in anatomical locations. Discrepancy regions of the grey matter volume and thickness where grey matter volume significantly decreased but without corresponding evidence of cortical thinning involved the rostral middle frontal, precentral, lateral occipital and superior frontal gyri. Subsequent region-of-interest analysis demonstrated that changes in surface area, grey/white matter intensity contrast and curvature accounted for the discrepancies. Our results suggest that the differences between grey matter volume and thickness could be jointly driven by surface area, grey/white matter intensity contrast and curvature.